Pemberdayaan Masyarakat Melalui Konversi Minyak Jelantah Menjadi Energi Terbarukan Berbasis Teknologi UCOllect di Desa Tonja - Pancane, I Wayan Dikse; Putri, Ni Luh Gek Idha Dyah; Suryadinatha, AAN. Oka; Adrama, Nyoman Gede; Suriana, I Wayan (Penerbit Widina, Widina Media Utama, 2025)
Inadequate management of used cooking oil has the potential to contaminate the environment, compromising water quality and public health. In Tonja Village, the limited awareness regarding the utilization of used cooking oil as a valuable raw material constitutes a significant challenge. This community service endeavor aims to enhance community awareness and engagement in the sustainable management of used cooking oil through educational initiatives and economic empowerment strategies. This initiative involves the dissemination of information and the facilitation of training in collaboration with Noovoleum ID, through the implementation of the